$1!X\!6-s - Zhong, Rong, active 502-519 (Salt Lake City, UT : Project Gutenberg, 2008)
"$1!X\!6-(B" by $1!DW !^!"&2 (Bis a critical examination of poetry written during the early 6th century. This work serves as a commentary on various poets and their contributions to Chinese literature, particularly focusing on the style and thematic significance of poetry. The book delves into the characteristics of poetry from different dynasties, illustrating the evolution of poetic forms and the importance of poetry in expressing emotions and social commentary. In "$1!X\!6-(B", the author categorizes numerous poets from ancient China, analyzing their styles, themes, and influences on the development of literature. Among the discussed poets are notable figures such as $1!Cs!_%(B, $1!K@!9x(B, and $1!_$!E](B, each representing different trends in poetry. The text meticulously articulates the merits and shortcomings of their works, emphasizing the virtue of balance between emotional depth and linguistic precision. Additionally, it explores the cultural context of poetry throughout dynasties, showing its function as a medium for both personal expression and broader societal reflections. Ultimately, "$1!X\!6-(B" is not only a celebration of poetic artistry but also a significant historical account of literary criticism in ancient China. (This is an automatically generated summary.)s
Release date is 2008-05-13
Produced by Shung Ru Wu
Keywords: Chinese poetry -- History and criticism